Evaluation of two way cross developed for free range poultry farming under farm and free range conditions - RAJKUMAR, U; HAUNSHI, S; PASWAN, C; PRAKASH, B; PADHI, M K; RAO, S V RAMA (The Indian Journal of Animal Sciences, 2019)
A comprehensive study was conducted to evaluate the performance of a two way cross developed for free range poultry farming under farm and field conditions. Chicks (412) produced by mating PD-1 males with PD-4 females in single hatch were utilized for the study. The data collected on 200 chicks from field and 193 chicks from farm were analysed to study the effect of system of rearing on growth and production performance. The body weights were significantly higher in males from 6–12 weeks of age revealing sexual dimorphism in birds both under farm and field conditions. The shanks were significantly longer in males. The mean dressing percentage was 68.51±2.82. Legs contributed 21.90±0.23% of live weight, followed by back, breast and wings. Abdominal fat proportion was 0.5% of body weight. The adult body weights were significantly higher in farm reared hens. The age at sexual maturity (ASM) was significantly higher in free range hens (205.12±18.23 days) compared to farm reared hens (152.35±1.03 days). The egg weights were significantly higher in farm reared birds at 40 and 52 weeks of age. The part period egg production up to 40 and 52 weeks of age was significantly higher in farm reared birds (69.22±3.89 and 122.54±4.64) than free range birds (43.42±4.62 and 83.74±8.12). The annual egg production (72 weeks) was 189.61±6.72 eggs in farm conditions. The peak production (17.12 eggs) reached at 25–28 weeks and maintained till 49–52 weeks of age in farm conditions. Under free range conditions, the peak production was attained at 37–40 weeks of age and maintained up to 45–48 weeks. It can be concluded that, the performance of the cross is quite encouraging under free range conditions with good growth rate and high production potential compared to indigenous/ native chickens, offering a bright scope as a promising dual purpose chicken variety for free range poultry.